First Nations workers picking strawberries, June 1943 - Staff Photographer Seattle Post-Intelligencer
In 1943, the Vashon Island Packing Company hired 80 First Nations people from British Columbia for the summer to weed and harvest strawberries, gooseberries, loganberries and currants. The Indian workers earned 50 to 60 cents an hour, reportedly two to three times what they might have made at home. Those who stayed the whole summer had their transportation to and from Canada paid as well. This June 1943 photo shows a number of First Nations workers from British Columbia picking strawberries on Vashon Island during World War II. They replaced Filipino workers who had done this work previously but were now growing vegetables and working in war industries. 1 negative: safety film, b&w; 4 x 5 in.